Qualitative and Quantitative Analysis of the Product and By-Products from Transesterification between Phenol and Dimethyl Carbonate - Tao Liu; Jing Hu; Li Yong; Gang Zhang; Yi Zhang; Tong Chen; Gongying Wang (Journal of Analytical Methods in Chemistry)
By-products (phenyl salicylate, phenyl 4-hydroxybenzoate, and xanthone) from transesterification between phenol and dimethyl carbonate (DMC) were qualitatively analyzed by gas chromatography-mass spectrometry, and a gas chromatographic method with directed injection for simultaneous quantitative analysis of the product (DPC) and by-products of the transesterification has been established. Based on the results of qualitative and quantitative analyses, the mechanism of the by-products generation was preliminarily deduced. The sample for quantitative analysis was directly diluted in acetone, and related compounds were separated on an HP-5 capillary column and detected by a hydrogen flame ionization detector (FID). The product and by-products were well separated, the correlation coefficients (r) within the concentration range of 1.0 μg/mL–100 μg/mL were ≥0.9997, the relative standard deviations were between 0.5% and 4.4%, spiked recoveries were between 91.5% and 105.6%, and detection limits were between 0.11 and 0.18 μg/mL. The established method is simple, rapid, accurate, sensitive, and highly specific. It is suitable for simultaneous qualitative and quantitative analyses of the product and by-products of transesterification between phenol and DMC.